Preferensi Mahasiswa UNP Terhadap Tempat Kos di kec. Padang Utara pada Masa Pandemi (Covid-19) dengan Menggunakan Analisis Konjoin - Lidia Bartasari; Arnellis Arnellis (Journal of Mathematics UNP, 2023)
Boarding house is primary needs for collage students who migrate. Each student has a different of preference in determining a place to stay or boarding house. This study aims to determine the combination of attribute levels from the level of preference of Padang State University students in choosing boarding houses in North Padang District.  The attributes used in this study are the distance to the boarding house, the rental price, and the boarding facilities The data analysis technique used is conjoint analysis.  The results showed that the combination of attribute levels that students preferred most in choosing a boarding house was a boarding distance of  km, the price range of boarding from IDR  to IDR and facilities of boarding prioritizing is Wi-Fi. Meanwhile, the combination of attribute levels that students dislike choosing a boarding house are boarding distances  km, the prices of boarding  IDR, and no facilities. The most important attribute for Padang State University students in choosing a boarding house is the boarding facility attribute because it has the highest relative importance value of 39.4%.